Effects of the program: “Salas para la paz”, on the degree of human development of individuals with drug addiction - González García, Héctor; Salazar Cantú, José de Jesús; Rodríguez Guajardo, Raymundo Cruz; Fernández Flores, Karla (Scientific research publishing, 2015)
This study estimates the impact that the program “Salas para la Paz” (Rooms for Peace), implemented by “Promoción de Paz, A.B.P.” (Peace Promotion, private association for beneficence), has on different aspects of human development, in individuals with addiction, in Monterrey, México. By testing mean differences and using propensity score matching, group comparisons are made, based on the time the subjects have been in the program. The study is based on information obtained from interviews conducted on the participants, and their families. Results based on the answers of the first group, reveal that the program has little or no effect whatsoever. On the other hand, the answers of the second group lead to mixed results, which tend to confirm that direct participant human development increases starting from the second month of treatment.